Global records of the invasive freshwater apple snail Pomacea canaliculata (Lamarck, 1822) - Seuffert, Maria Emilia (2024)
This database comprises occurrence data, including both specimen and observation data, obtained from the whole distribution range (native and invaded) for the freshwater snail Pomacea canaliculata (Caenogastropoda: Ampullariidae). This species is native from lower Del Plata basin in South America but, together with other congeners collectively known as "apple snails", were introduced to many regions outside their natural ranges where they rapidly spread out, causing serious damage to aquatic crops and also to biodiversity and functioning of natural wetlands. The aim of this data publication is to provide an open access, updated and accurate database of P. canaliculata records worldwide, available for use in ecological studies and pest management, focusing on discriminate misidentifications with other apple snails. This database includes 718 records of P. canaliculata from 29 countries distributed in Africa, South America, North America, Asia and Pacific Islands, and were reported from the early 20th century until present day. The records reported here were compiled from different sources: - Our personal records which include samples collected during the past 25 years covering a large area of many provinces in Argentina. - Available bibliography, searching for any reliable report mentioning geographic coordinates or at least a precise locality, excluding those with doubtful identity or not determined records such as “Pomacea” or “Pomacea sp.”. - By request to several researchers with expertise in this species around the world to provide us records and also their expert opinion to discard records corresponding to other congeners (especially the often-confounded P. maculata).